Articulate storyline integration in Ethnosmart learning media development - Rendi Rama Dayu; Selvi Loviana (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Mathematics is a subject with varying levels of difficulty in each topic. Some concepts can be understood directly, while others are abstract and require learning media to facilitate understanding. The development of learning media at the junior high school (SMP) level is essential, as many students still experience difficulties in learning mathematics without adequate media support. Interactive media can serve as an effective tool to support students’ understanding, especially in social arithmetic material. This research aims to develop ethnomathematics-based learning media using Articulate Storyline (EthnoSmart) that meets validity and practicality criteria. The research employed a research and development method using a 4D model. The trial was conducted on grade VIII junior high school students. The research instruments included interview guides, media selection questionnaires, validation sheets, and student response questionnaires. Data analysis was carried out to determine the validity and practicality levels of the product. The results of evaluations by material experts, media experts, and cultural experts indicate that the developed media meets valid criteria. Students’ responses also show that EthnoSmart meets practical criteria. These findings indicate that ethnomathematics-based learning media using Articulate Storyline is appropriate for use in mathematics learning. In conclusion, EthnoSmart is a feasible and user-friendly learning medium that supports students’ understanding of social arithmetic concepts. This study contributes to the development of culturally responsive and interactive digital learning media by integrating ethnomathematics with modern technology, providing an alternative approach to enhance meaningful mathematics learning.